2019
DOI: 10.1002/art.40899
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Physical Activity and Subsequent Risk for Rheumatoid Arthritis Among Women: A Prospective Cohort Study

Abstract: Objective To evaluate the effects of long‐term physical activity on subsequent risk of rheumatoid arthritis (RA) in a prospective cohort study. Methods This study investigated physical activity and RA risk among women from the Nurses' Health Study II (1989–2015). Physical activity exposures and covariates were prospectively obtained using biennial questionnaires. Two rheumatologists independently reviewed the medical records of women who self‐reported a new diagnosis of RA on biennial questionnaires and who sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…Because excess weight to a large degree is driven by diet and lifestyle factors 56 , it is possible that certain lifestyle-related risk factors (e.g. consumption of sugar-sweetened soft drinks and low physical activity) may contribute to the development of rheumatoid arthritis partly through an effect on adiposity 52 , 57 59 , and further studies are needed to clarify if this is the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because excess weight to a large degree is driven by diet and lifestyle factors 56 , it is possible that certain lifestyle-related risk factors (e.g. consumption of sugar-sweetened soft drinks and low physical activity) may contribute to the development of rheumatoid arthritis partly through an effect on adiposity 52 , 57 59 , and further studies are needed to clarify if this is the case.…”
Section: Discussionmentioning
confidence: 99%
“…Established or suspected risk factors for rheumatoid arthritis include age 7 , genetic predisposition (human leukocyte antigen (HLA)-DR4) 8 , smoking 9 , 10 , diet 10 12 , physical activity 13 , and obesity 14 – 24 . In addition, the global prevalence of rheumatoid arthritis has been reported to be approximately two times higher in women than in men 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Only very few studies have been performed investigating effects of exercise on risk for RA development, and the largest one so far from our own groups failed to demonstrate any protective effects on disease incidence, but showed that individuals involved with regular exercise programmes before onset of RA had a significantly milder disease at onset as compared with individuals with a sedentary lifestyle [137]. In a recent study from the Nurses' Health Study, higher levels of physical activity were, however, associated with reduced RA risk [138].…”
Section: Effects Of Exercisementioning
confidence: 99%
“…Even so, the disease activity measurements were performed by different trained evaluators who were unaware of the specific therapeutic regimen to make the study more objective. Second, previous studies demonstrated that metabolic factors, including dietary intake and physical activity, were associated with the occurrence and disease activity [34][35][36] . However, as the setup of the parameters was mainly focused on the change in RA disease activity before and after treatment, data on these metabolic factors were not collected in this study.…”
Section: Discussionmentioning
confidence: 99%